Viral hepatitis and the immunological response: a review - F. M. Godoy, Francielle; A. Cerni , Felipe; B. Pucca , Manuela; C. Ferreira, Ana Iara (Revista Saúde & Diversidade, 2017)
Introduction: In Brazil, viral hepatitis is infectious disease of compulsory notification and is considered a serious public health problem. Infections with A, B, C, D or E viruses trigger the activation of immune system molecules and cells at the level of innate and acquired immunity. Objective: The present study aimed to review the knowledge about viral hepatitis and the immune system's performance against these infections. Methods: This is a literature overview from academic books and scientific articles available in the Scientific Electronic Library Online, US National Library of Medicine National Institutes of Health and Google Scholar databases. Having as key words hepatitis A, hepatitis B, hepatitis C, hepatitis D, hepatitis E and immune system. The relevant articles corresponding to the period between 1974 and 2017 were selected. Development: Viral hepatitis is characterized by inflammation in liver cells caused by groups of viruses that have hepatotropism in common. The diagnosis is made through serological methods and molecular biology techniques. The approach of the immune system in relation to the combat of this infection follows same particularities. Conclusion: This review demonstrated that the determination of the etiologic agent is essential for the conduct to be taken with the infected individual. Moreover, the immune system is directed related to the viruses elimination, presenting some particularities. In addition, this review highlights that the vaccination is the main responsible for reducing people infected by viruses A and B.